Universal access to essential health information: accelerating progress towards universal health coverage and other SDG health targets - Neil Pakenham-Walsh; Geoff Royston; Chris Zielinski (BMJ Global Health)
The information that people need to protect and manage their own health and the health of those for whom they are responsible is a fundamental element of an effective people-centred healthcare system. Achieving universal health coverage (UHC) requires universal access to essential health information. While it was recently recognised by the World Medical Association, universal access to essential health information is not yet reflected in official monitoring of progress on UHC for the sustainable development goals (SDGs). In this paper, we outline key features that characterise universal access to essential health information and indicate how it is increasingly achievable. We highlight the growing evidence of the impact of wider access to practical and actionable information on health for the public, carers and frontline health workers and provide illustrative, evidence-based, examples of how increasing access to essential health information can accelerate the achievement of UHC and other health targets of the SDGs. The paper ends with an assessment of reasons why universal access to essential health information has not yet been achieved, and an associated call to action to key stakeholders—such as governments, multilaterals, funding bodies, policy-makers, health professionals and knowledge intermediaries—to explicitly recognise the foundational role of universal access to essential health information for achieving UHC and the rest of the health SDGs, to include it in the relevant SDG target and associated monitoring indicators, and to incorporate actions in their own policies and programmes to promote and enable this access.